Memória, intertextualidade, literatura e semiótica: a tragédia e o trágico em Sandman - Piovesan, Attila de Oliveira (2010)
This work investigates the relationship between literature and Neil Gaiman’s The Sandman comic book. To link these arts, we describe the beginning of the superhero comics industry, its development, the roots of both crime and horror as popular literary genres and the criticism that lead to comics censorship and its subsequent overcoming – slowly making possible a new kind of discourse in comic books, an open dialogue with the literary world. Understanding that the concepts of semiosis, intertextuality and intermediality can act as literary – and cultural – memory transmitters, we adopt Charles S. Peirce’s semiotics to establish the semiosic chaining of the orphic myth. Furthermore, we follow the transformation of tragedy (literary concept) into tragic (a philosophical notion) and its function in The Sandman’s narrative and the path of Morpheus, the doomed hero.